Study of preoperative GnRh agonist in cutaneous scar endometriosis - Kulkarni, Nitin Naresh; Patil, Alka Bhaurao; Patel, Richa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Cutaneous scar endometriosis is an uncommon pathology, it is rare and difficult to diagnose, mostly follows obstetrical and gynaecological surgeries. Surgical wide excision is the mainstay of treatment. The objective of this study was to evaluate efficacy of preoperative GnRh agonist in scar endometriosis. Methods: This is prospective randomized case control study performed on all cutaneous scar endometriosis cases reporting to our institute as well as consultants from Dhule obstetrics and gynaecology society. All cases were operated and follow up in our institute by same surgeon. Results: Surgical excision accompanied by preoperative GnRh agonist therapy is helpful for easy excision and reduce recurrence of scar endometriosis. Conclusions: Abdominal scar endometriosis is rare gynecological pathology, should be suspected in any women of child bearing age group complaining of cyclical painful nodule in scar following a previous obstetric and gynaecological procedure.